Catalytic Enantioselective Cloke–Wilson Rearrangement. Issue 27 (4th June 2018) - Ortega, Alesandere; Manzano, Rubén; Uria, Uxue; Carrillo, Luisa; Reyes, Efraim; Tejero, Tomas; Merino, Pedro; Vicario, Jose L.
Abstract: Racemic cyclopropyl ketones undergo enantioselective rearrangement to deliver the corresponding dihydrofurans in the presence of a chiral phosphoric acid as the catalyst. The reaction involves activation of the donor‐acceptor cyclopropane substrate by the chiral Brønsted acid catalyst to promote the ring‐opening event, thus generating a carbocationic intermediate that subsequently undergoes cyclization. Computational studies and control experiments support this mechanistic pathway. Abstract : A paired rearrangement : Racemic cyclopropyl ketones undergo enantioselective rearrangement to deliver dihydrofurans in the presence of a chiral phosphoric acid catalyst. The reaction involves activation of the donor‐acceptor cyclopropane by the Brønsted acid catalyst to promote the ring‐opening event, thus generating a carbocationic intermediate that subsequently undergoes cyclization. EDG=electron‐donating group.